THE ANALYSIS OF RADIATION DOSE ON REPRODUCTIVE ORGAN IN ANTEROPOSTERIOR PROJECTION ABDOMEN RADIOGRAPHY USING 10 kV RULES METHOD - Bagus Dwi Handoko; Mohammad Alif Nurfathoni; Akhmad Haris Sulistyadi (Jurnal Imejing Diagnostik (JImeD), 2019)
Background: Abdomen radiography is a radiographic examination procedure in the abdominal area to show abnormalities that occur in the tractus digestivus / gastrointestinal. Radiographic examination of the abdomen is directly related to the reproductive organs that are sensitive to radiation. The purpose of this study was to find out the optimization technique of AP projection radiographic Abdomen examination with the 10 kV rule method, knowing the radiation dose received by the reproductive organs using the 10 kV rule method, knowing the quality of radiographs produced on AP projection radiographic examination using the 10 kV rule method.Methods: Jenis penelitian yang digunakan adalah penelitian Pre Eksperimental yaitu dengan melakukan pengukuran terhadap kualitas hasil radiograf dengan metode kenaikan 10 kVruledisertai penurunan mAs 50%. Pengukuran dosis radiasi dengan menggunakan alat ukur radiasi ray safe X-2, sedangkan untuk pengukuran kualitas dilakukan secara kuantitatif nilai pixel value dan visual citra.Method: The type of research used in this study is Pre Experimental research, namely by measuring the quality of the results of the radiograph by increasing the method of 10 kV rule with a decrease of 50% mAs.Results :The results of radiation dose measurements received by the AP projection reproductive organs with standard exposure factors (1) are kV 70 and mAs 32 is 8.33 mGy. In the exposure factor (2) kV 80 and mAs 16 is 5.50 mGy. Exposure factor (3) with kV 90 and mAs 8 radiation doses received at reproductive organs are 3.47 mGy and exposure factor (4) with kV 90 and mAs 4 produce radiation doses of 1.18 mGy. The highest contrast value (Δ pixel value) of each exposure factor is the exposure factor (2) kV 80 mAs 16, then the exposure factor (3) kV 90 mAs 8. The lowest Contrast value ((pixel value) is the exposure factor. (4) kV 100 mAs 4. The results of radiographic quality assessment on Abdomen examination of AP projection show that by visual assessment of radiographic specialists showed that the exposure factor that produced the most optimal Abdomen radiography was exposure factor 3 at kV 90 and mAs 8.Conclusion: Optimal abdominal radiographic examination with a low radiation dose can use exposure factors of kV 80 mAs 16 and kV 90 mAs 8.